2004
DOI: 10.1001/archotol.130.2.149
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neck Dissection on Health-Related Quality of Life

Abstract: Objective: To compare health-related quality of life in patients having no neck dissection and those having a selective dissection, with particular reference to shoulder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 16 publications
4
82
1
1
Order By: Relevance
“…Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15. Therefore, determining a rational extent of therapeutic LND is vital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15. Therefore, determining a rational extent of therapeutic LND is vital.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the above reasons and the prognostic significance, it is universally agreed that therapeutic LND should include at least a comprehensive but selective LND of levels II–IV. However, whether therapeutic LND should routinely include level V lymphadenectomy remains controversial 13, 14, 15, 16, 17, 18, 19, 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar improvement in shoulder function was observed in a study done by Lavericks who compared the neck dissec tion unilateral vs bilateral with patients treated without the neck dissection. 11 Twelve patients reported that they had difficulty in lifting weights, five of whom had pain in shoulder or neck. This may be due to nonfunctioning spinal acce ssory nerve, lack of physiotherapy and some amount of shoulder joint capsulitis.…”
mentioning
confidence: 99%